1987
DOI: 10.1111/j.1365-2044.1987.tb03976.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of etomidate and propofol for anaesthesia in microlaryngeal surgery

Abstract: Propofol and etomidate were compared as hypnotics in total intravenous anaesthesia for microlaryngeal surgery combined with jet ventilation. Two groups of 15 patients were studied. In group 1, propofol 2.0 mg/kg was used for induction. For maintenance a continuous infusion of 12 mg/kg/hour was used for the first 10 minutes, followed by 9 mg/kg/hour for the next 10 minutes and 6 mg/kg/hour thereafter. In group 2, the induction dose of etomidate was 0.3 mg/kg followed by continuous infusion of 1.8 mg/kg/hour for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 14 publications
4
18
0
1
Order By: Relevance
“…9 This drug has been shown to obtund airway reflexes and allow a relatively easy intubation in the majority of patients. 10 Similar results with the same induction technique as used in this study have been reported previously in non-myasthenic patients. 10,11 MG patients are also more sensitive than normal to neuromuscular depression by volatile anesthetic agents such as halothane and isoflurane.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…9 This drug has been shown to obtund airway reflexes and allow a relatively easy intubation in the majority of patients. 10 Similar results with the same induction technique as used in this study have been reported previously in non-myasthenic patients. 10,11 MG patients are also more sensitive than normal to neuromuscular depression by volatile anesthetic agents such as halothane and isoflurane.…”
Section: Discussionsupporting
confidence: 89%
“…10 Similar results with the same induction technique as used in this study have been reported previously in non-myasthenic patients. 10,11 MG patients are also more sensitive than normal to neuromuscular depression by volatile anesthetic agents such as halothane and isoflurane. [12][13][14] In our series, neuromuscular trasmission during surgery was more depressed with the use of sevoflurane compared with propofol, but it recovered completely at the end of anesthesia so that the mean ) extubation and mean ) awake were similar in both groups.…”
Section: Discussionsupporting
confidence: 89%
“…[23] Various anesthetic agents and a number of alternative anesthetic techniques have been tried with varying results. [46] The use of intravenous anesthesia with propofol during microlaryngeal surgery is in widespread clinical practice due to its rapidity and quality of awakening. [7–9]…”
Section: Introductionmentioning
confidence: 99%
“…In surgery requiring intravenous anesthesia without intubation in laryngomicrosurgery, TIVA for anesthesia has been reported to use propofol alone [11], narcotic analgesia and propofol [12], and a combination of propofol and fentanyl [13].…”
Section: Discussionmentioning
confidence: 99%